First person state/psychological imagery modulates the orbital frontal gyrus and the putamen in individuals with depression - Tomasino, Barbara; Piani, Maria Chiara; Maggioni, Eleonora; Bonivento, Carolina; D’Agostini, Serena; Balestrieri, Matteo; Brambilla, Paolo (Frontiers in Psychiatry, 2025)
BackgroundPatients with depression appear to imagine scenes preferentially from a 3rd person perspective as if they were observers. Methods: By using functional magnetic resonance imaging we asked patients with major depressive disorder (19, MDD) and healthy controls (19, HC) to imagine 1st person perspective state/psychological (vs. action) scenes.ResultsWe found that the left superior frontal gyrus (orbital part) and the right putamen were differentially activated by the state/psychological (vs. action) imagery (vs. letter detection) in MDD individuals vs. HC.DiscussionWe suggest that imagery for state/psychological events increased activation in areas involved in self-related processing and personal perspective changes.